2020
DOI: 10.1177/0098628320959923
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Expectations and Students’ Satisfaction: The Mediating Role of Excellent Teacher Behaviors

Abstract: This study sought to investigate whether teacher behaviors, within the Teacher Behavior Checklist dimensions of caring and supportive and professional competency and communication skills, relate to students’ satisfaction. Additionally, it assessed the influence of the importance students set on teacher behaviors on students’ satisfaction. Cross-sectional survey data were analyzed using hierarchical linear regression and mediation analysis. Results suggested teacher behaviors within the caring and supportive di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Lecturer behaviour can have a major impact on student's motivation to learn. [26] Italian students in large number agree that online teaching is better than traditional and their satisfaction with this way of learning is high. [27] Table 7 shows the disadvantages that can cause difficulties in learning, also through a Likert scale.…”
Section: Results and Discusionmentioning
confidence: 99%
“…Lecturer behaviour can have a major impact on student's motivation to learn. [26] Italian students in large number agree that online teaching is better than traditional and their satisfaction with this way of learning is high. [27] Table 7 shows the disadvantages that can cause difficulties in learning, also through a Likert scale.…”
Section: Results and Discusionmentioning
confidence: 99%
“…To my knowledge, the indirect relationship between TBC importance and students' effort through TBC behaviors has not been explored within a semester. Geier (2020) found evidence that teacher behaviors, as rated with the TBC, mediate the relationship of students' importance of teacher behaviors with students' satisfaction. This study proposes the same mediation process with the outcome of the students' effort.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 94%
“…First, it provides further empirical evidence that expectations of students matter toward teacher behaviors. Geier (2020) found evidence that teacher behaviors, rated using the TBC, mediate the relationship between students' expectations and students' satisfaction. This study also found a mediation, therefore, confirming the finding Geier (2020) but using a different outcome.…”
Section: Theoretical Implicationsmentioning
confidence: 94%
See 2 more Smart Citations